Poly(Lactic) acid reinforced with alkaline Lignin Biocomposites prepared by Thermal Extrusion for sustainable 3D printing process - Abd Rahman, Nurul Amirah; Anuar, Hazleen; Ali, Fathilah; Suhr, Jonghwan (IOP Publishing Ltd, 2021)
The focus of this work is the mechanical characterization of biomaterials produced by 3D printing based on fused filament fabrication (FFF) process that has been mainly used for prototype rather than functional components due to the limited mechanical properties of pure thermoplastics parts. Addition of reinforcements from natural fiber has been adopted to improve the mechanical properties of the 3D printed parts. In this study, alkaline lignin powder that has been extracted from oil palm empty fruit bunches (OPEFB) via alkaline extraction process were used as filler in the production of biocomposites with poly(lactic) acid (PLA). Poly(lactic) acid filaments filled with 1% of alkaline lignin powder and has been compared with the presence of 5% of epoxidized palm oil (EPO) by means of thermal extrusion and further proceed with 3D printing. The samples were mechanically characterized using tensile tests and the fractography were observed. Tensile test that has been done on the filaments reveal that the filament with addition of lignin and EPO shows improved mechanical properties with higher tensile strength as well as lower stiffness. The 3D printed samples of the filament compositions also exhibit similar trend where the said filament has the best mechanical properties when the EPO is incorporated in the filament.